Redox Properties of Peat Particulate Organic Matter: Quantification of Electron Accepting Capacities and Assessment of Electron Transfer Reversibility. Issue 8 (21st August 2021) - Joshi, Prachi; Schroth, Martin H.; Sander, Michael
Abstract: Peat particulate organic matter (POM) has been hypothesized to act as a terminal electron acceptor (TEA) for anaerobic microbial respiration in northern peatlands, thereby lowering dissolved methane (CH4 ) concentrations in these systems. However, the redox properties of peat POM and an assessment of its redox state in situ remain missing, mainly due to the lack of an accurate analytical approach to quantify the number of electrons that are transferred to/from POM. Here, we first developed a new spectrophotometric method to quantify the number of electrons that are transferable to peat POM—denoted hereafter as electron accepting capacity (EAC)—by reacting POM with the reduced species of the probe compound 4, 4'‐bipyridinium‐1, 1'bis(2‐ethylsulfonate). Second, we used this analytical approach to quantify the EAC of an oxidized reference POM material (0.38 ± 0.039 mmol e − /g POM) and of redox‐preserved POM from three ombrotrophic bogs in Värmland, Sweden (0.17–0.24 mmol e − /g POM). These EAC values are substantially higher than previous estimates, likely reflecting kinetic artifacts in previous analytical methods. We further established reversible electron transfer to the oxic reference POM over a cycle of electrochemical reduction and O2 re‐oxidation. Finally, we determined that the EAC of two of the three bog POM samples that were collected anoxically (i.e., redox state‐preserved POM) increased by ∼0.09 mmol e − /g POM upon exposure to air for 8 days, demonstrating that the POM was indeed reduced in situ . Collectively, our results strongly support that POM acts as a sustainable TEA in northern peatlands, which may lower methane release from these systems. Plain Language Summary: Northern peatlands have accumulated significant amounts of peat organic matter since the last glaciation and now store a significant portion of the total global soil organic carbon. Global warming has triggered interest in understanding organic matter breakdown processes in northern peatland soils which result in the release of stored carbon, particularly in form of the potent warming gas methane (CH4 ). Past studies provided evidence that some anaerobic microorganisms respire organic substrates and transfer liberated reducing equivalents (i.e., electrons) to peat particulate organic matter (POM), a respiration pathway that lowers CH4 concentrations. Herein, we developed a new analytical method based on spectrophotometric measurements to quantify how many electrons POM accepts. Applying this method to peat POM from Swedish peat bogs, we found that all tested POM accept electrons. Moreover, we demonstrated that electron transfer to peat POM was largely reversible when the reduced POM was exposed to air. These findings suggest that peat POM at oxic‐anoxic interfaces may be reduced and re‐oxidized cyclically, a process that may decrease the amount of CH4 released from peat soils. The POM redox properties determined herein will help advance a more accurate understanding of organic matter breakdown as well as CH4 dynamics in northern peatlands. Key Points: A new method was developed to measure the electron accepting capacity (EAC) of peat particulate organic matter (POM) The measured EAC of POM was 0.17–0.38 mmol e − /g POM, substantially higher than previous estimates Electron transfer to POM was observed to be reversible and bog POM was demonstrated to be reduced in situ